EXAMINATION OF THE WASTE RESULTING FROM SEED COTTON CLEANING (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The article presents a dynamic model that explains how impurities pass through cotton's bulk and attach themselves to it elastically. Patterns in the movement of the particles inside and on the surface of the cotton mass because of the forces acting on them have been detected based on the cleaning drum's parameters. The forces exerted on the particle can be expressed by the cleaning drum's radius and angular velocity.